Barriers and Prospects for Arbitration in Resolving Disputes in the Indonesian Coffee Industry - Ahmad Widad Muntazhor; Tetri Mutiara Afsaloka; Muhammad Brillyan Alfayedo (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The Indonesian coffee industry makes a substantial contribution to the national economy. However, the complexity of business relationships across its supply chain increases the likelihood of disputes, highlighting the need for effective and equitable dispute resolution mechanisms. This study examines the role of arbitration as a dispute resolution forum in the Indonesian coffee industry, analyzes its jurisdiction over both domestic and international commercial disputes, and identifies the barriers that limit business actors access to arbitration. The research employs a normative legal methodology using statutory, conceptual, comparative, and case-based approaches through an extensive review of primary, secondary, and tertiary legal sources. The findings demonstrate that arbitration is supported by a robust legal framework and offers several advantages, including procedural efficiency, confidentiality, and legal certainty, making it well suited to the unique characteristics of the coffee industry. Nevertheless, its effectiveness remains constrained by limited legal awareness, high arbitration costs, unequal bargaining power among parties, and institutional challenges. Accordingly, strengthening the regulatory framework and developing more inclusive, accessible, and cost-effective arbitration mechanisms are essential to enhance the sustainability and global competitiveness of Indonesias coffee industry.